Detection of Mechanical Heart Valve Thrombosis Using Support Vector Machine - Sabri ALTUNKAYA; Onur INAN (International Journal of Applied Methods in Electronics and Computers, 2019)
Thrombosis on the valve that prevents the movement of mechanical heart valves is a fatal disease requiring urgent intervention. Thrombosis is detected by echocardiographic findings and/or CT images. In this study, it has been tried to determine the formation of thrombosis by listening method which has been used for controlling the functionality of the heart valves for years. For this firstly heart sounds of patients with thrombosis and normal mechanical heart valves were recorded. Then the first and second heart sounds (S1 and S2) were separated from the recorded sounds. After the frequency spectrum of S1 and S2 were found using autoregressive spectrum estimation methods, six features were obtained regarding the frequency components. Then the features obtained are classified by support vector machine methods. The accuracy value was found to be 100% by using the 3 fold cross-validation. The average accuracy is 95.18% as a result of running the classifier 500 times using 3 fold-cross validation.